2015
DOI: 10.1038/srep16333
|View full text |Cite
|
Sign up to set email alerts
|

Muscle tissue engineering and regeneration through epigenetic reprogramming and scaffold manipulation

Abstract: Efficiency of cell-based tissue engineering and regenerative medicine has been limited by inadequate cellular responses to injury because of aging and poor controllability of cellular interactions. Since cell progression is under a tight epigenetic regulation, epigenetic modulators such as 5-azacytidine (5-Aza-CR) have been utilized to facilitate reprogramming and development of somatic cells in 2-dimensional (2-D) settings. Nonetheless, progression of a specific tissue lineage toward the terminal phenotype is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 62 publications
(83 reference statements)
2
20
0
Order By: Relevance
“…Thanks to its powerful effects, this compound may be used to increase chromatin plasticity and facilitate phenotype changes1213. Several studies reported 5-aza-CR ability to facilitate adult somatic cell switch from one phenotype to a different one141516. In particular, we demonstrated that a short exposure to 5-aza-CR allows a transient passage through a plastic chromatin state.…”
mentioning
confidence: 61%
“…Thanks to its powerful effects, this compound may be used to increase chromatin plasticity and facilitate phenotype changes1213. Several studies reported 5-aza-CR ability to facilitate adult somatic cell switch from one phenotype to a different one141516. In particular, we demonstrated that a short exposure to 5-aza-CR allows a transient passage through a plastic chromatin state.…”
mentioning
confidence: 61%
“…Compared to other types of mesenchymal stem cells, ADSCs possess the highest proliferation potential and exhibit high tolerance to serum deprivation-induced apoptosis 41 . Moreover, ADSCs can be successfully induced to differentiate into myoblasts by 5-azacytidine and have been reported to treat muscle disorders by our group and others 19 , 42 , 43 . In our experiments, we took autologous ADSCs as seed cells, promoted their muscle differentiation with 10 μM 5-azacytidine and 5% horse serum, and built the muscular layer of bionic urethras.…”
Section: Discussionmentioning
confidence: 94%
“…Myogenin has been extensively reported to be a late marker of myoblast fusion, required for terminal differentiation ( Tan et al, 2015 ). Mudera et al (2010) and Smith et al (2012) demonstrated the expression pattern of MYOG in similar tissue engineered models, where comparisons were made against 2D controls.…”
Section: Discussionmentioning
confidence: 99%